Answer:
The difference between the area of the original triangle and the area of the new triangle is [tex]\Delta A_{\bigtriangleup} = \frac{5}{2}\cdot (3\cdot x +7)\cdot (5\cdot x -1)[/tex].
Step-by-step explanation:
The equation for the area of a triangle ([tex]A_{\bigtriangleup}[/tex]) is:
[tex]A_{\bigtriangleup} = \frac{1}{2}\cdot b \cdot h[/tex]
Where:
[tex]b[/tex] - Base, dimensionless.
[tex]h[/tex] - Height, dimensionless.
The expression for each triangle are described below:
First Triangle ([tex]b = 3\cdot x + 7[/tex], [tex]h = 5\cdot x - 1[/tex])
[tex]A_{\bigtriangleup,1} = \frac{1}{2}\cdot (3\cdot x+7)\cdot (5\cdot x -1)[/tex]
Second Triangle ([tex]b = 3\cdot (3\cdot x+7)[/tex], [tex]h = 2\cdot (5\cdot x -1)[/tex])
[tex]A_{\bigtriangleup,2} = 3\cdot (3\cdot x+7)\cdot (5\cdot x -1)[/tex]
The difference between the area of the original triangle and the area of the new triangle is:
[tex]\Delta A_{\bigtriangleup} = A_{\bigtriangleup,2}-A_{\bigtriangleup,1}[/tex]
[tex]\Delta A_{\bigtriangleup} = 3\cdot (3\cdot x+7)\cdot (5\cdot x-1)-\frac{1}{2} \cdot (3\cdot x+7)\cdot (5\cdot x-1)[/tex]
[tex]\Delta A_{\bigtriangleup} = \frac{5}{2}\cdot (3\cdot x +7)\cdot (5\cdot x -1)[/tex]
The difference between the area of the original triangle and the area of the new triangle is [tex]\Delta A_{\bigtriangleup} = \frac{5}{2}\cdot (3\cdot x +7)\cdot (5\cdot x -1)[/tex].